Prostatic Abscess Combined With Spleen Abscess Due to Multi-Drug-Resistant Gram-Negative Bacilli: A Case Report and Literature Review - Shun Li; Zeqiang Sun; Ning Di; Qingyong Liu; Fei Wu (American Journal of Men's Health, 2022)
The prostatic abscess is a rare complication of a bacterial infection of the prostate. Since the early use of potent antibiotics to treat urinary tract infections, the incidence of the prostatic abscess has declined significantly. In keeping with that, prostatic abscess combined with abscesses in the spleen or other distant organs become an extremely rare but fatal clinical condition. Here, we present a case of prostate and spleen abscess due to multi-drug-resistant gram-negative bacilli without obvious risk factors. The patient initially complained of high-grade fever and dysuria. After screening the source of infection by computed tomography (CT) scans, prostate and spleen abscesses were diagnosed. In addition, extended-spectrum beta-lactamase positive Escherichia coli was detected both in urine and blood culture. The patient was successfully treated by a transurethral resection of the prostate followed by splenic puncture and drainage, as well as intravenous administration of meropenem. Although the prostate abscess combined with spleen abscess was rare, the possibility of dissemination in remote tissues should be taken into consideration before the surgical treatment of prostatic abscesses. The concurrent drainage of multiple abscesses followed by intensive and sensitive antibiotics was safe and effective for indicated patients.